Waleed Saleh. 2022. Feminismo e islam: una ecuación imposible. Sevilla: El Paseo. 168 pp. ISBN 9788419188038 - Gutiérrez de Terán Gómez-Benita, Ignacio (Estudios de Asia y África, 2023)
Waleed Saleh. 2022. Feminismo e islam: una ecuación imposible. Sevilla: El Paseo. 168 pp. ISBN 9788419188038